A framework for selecting the optimal technique suitable for application in a data mining task - Chiroma, Haruna; Abdul-Kareem, Sameem; Abubakar, Adamu (SpringerLink, 2013)
This paper presents a conceptual framework for selection of data mining technique based on the 8 selection criteria’s: optimization capability, computation complexity, flexibility, interpretability, scalability, ease of problem encoding, autonomy, and accessibility. The framework is suitable for choosing appropriate technique for application in a particular task of data mining. The paper has set the stage for further research work.